Common Ground, Common Future : Moral Agency in Public Administration, Professions, and Citizenship. - Garofalo, Charles (CRC Press, 2005)
The inherently moral nature of public administration, argue the authors (of Texas State U.), makes the public administrator as a moral agent a moral exemplar for other professions. They examine a unified ethic that is implied by this view of public administration and consider its application to other professions, including business, medicine, highe.